Identiﬁcation, functional characterization and expression pattern of myeloid differentiation factor 88 (MyD88) in Nibea albiflora. Issue 124 (May 2022) - Tang, Xiuqin; Yang, Meijun; Liu, Jiaxin; Zheng, Libing; Xu, Dongdong; Chi, Changfeng; Lv, Zhenming; Liu, Huihui
Abstract: Myeloid differentiation factor 88 (MyD88), composed of an N-terminal death domain and a C-terminal Toll/interleukin (IL)-IR homology domain, is a key connector protein in the TLR signal transduction pathway. In this study a novel isoform of MyD88 in Nibea albiflora (named as NaMyD88) was identified and functionally characterized (GenBank accession no. MN384261.1). Its complete cDNA sequence was 1672 bp and contained an open reading frame of 879 bp encoding 292 amino acid residues, which was similar to its teleost fish counterparts in the length. The theoretical molecular mass was 33.63 kDa and the isoelectric point was 5.24. BLASTp analysis suggested that the deduced amino acids sequence of NaMyD88 shared high identity to the known MyD88, for instance, 94.77% identity with Collichthys lucidus . Sequence analysis showed that NaMyD88 protein was consistent with MyD88 protein of other species at three conserved domains, N-terminal DD, short middle domain and C-terminal TIR, and the TIR domain contained three highly conserved motifs: Box1, Box2, and Box3. NaMyD88 and red fluorescent protein (Dsred) were fused and expressed in the cytoplasm of the epithelioma papulosum cyprini (EPC cells). The NaTLR9-TIR-EGFP fusion protein, which was obtained in our previous studies, showed green fluorescence and mainly distributed in the cytoplasm. After co-transfection, NaMyD88-Dsred and NaTLR9-TIR-EGFP obviously overlapped and displayed orange-yellow color. The results showed that the homologous MyD88-Dsred could interact with NaTLR9-TIR-EGFP. Based on this result pcMV-NaMyD88-TIR-Myc plasmids and the pcDNA3.1-NaTLR9-TIR-flag were constructed and co-transfected into 293T cells for the immunoprecipitation test. According to Western blot, the protein eluted by Flag-beads could be detected by anti-Flag-tag antibody and anti-Myc tag antibody respectively, while the protein without NaTLR9-TIR could not be found, which further proved that TLR and MyD88 could interact each other. The prokaryotic plasmid of MyD88-TIR domain was constructed, expressed in BL21 (DE3) and purified by Ni-NAT super flow resin conforming to the expected molecular weight of 27 kDa with the corresponding active sites for its conferring protein-protein interaction functions. Real-time fluorescence quantitative PCR showed that NaMyD88 could be expressed in intestine, stomach, liver, kidney, gill, heart and spleen, with the highest in the kidney, and it was up-regulated after being infected with Polyinosinic:polycytidylic acid - Poly (I:C) and Pseudomonas plecoglossicida, which showed that NaMyD88 was involved in the immune response of N.albiflora . These data afforded a basis for understanding the role of NaMyD88 in the TLR signaling pathway of N.albiflora . Highlights: A MyD88 homologue was identified from Nibea albiflora (NaMyD88). The functional domains in NaMyD88 were highly conserved and located in cytoplasm. There was the interaction between MyD88 and NaTLR9 for Toll/NF-κB pathway. NaMyD88 could be significantly induced in response to bacteria and viruses infection. NaMyD88 played an important role in the TLR signaling pathway.